How Beef, Chicken, and Egg Demand Elasticities Vary with Income in Indonesia - Rulianda Purnomo Wibowo; Dian Pebriyani; Titien Indrawati; Muhammad Khaliqi (Jurnal AGRISEP, 2025)
Regional economic factors, income levels, and the availability of substitutes influence the demand for beef, chicken, and eggs in Indonesia. Beef is considered a luxury commodity in higher-income areas and exhibits greater price sensitivity in lower-GDP regions. Chicken, a staple protein source, generally demonstrates inelastic demand but increases price sensitivity in the lower GDP areas. Eggs, being more affordable, exhibit higher price elasticity, particularly in lower-GDP regions, and often complement beef consumption. This study examines the own-price, cross-price, and income elasticities for beef, chicken, and eggs in Indonesia, comparing these effects across provinces with varying income per capita levels. The research utilized secondary data from the Central Statistics Agency, encompassing per capita commodity consumption, consumption values, and prices from 2013 to 2023 across 33 provinces. The Almost Ideal Demand System (AIDS) model analyzed the interrelated consumption of beef, broiler chicken, and eggs. Certain provinces were excluded due to data limitations, particularly in newly formed regions with insufficient historical records. The findings of this research indicate that price sensitivity, regional economic factors, and consumer preferences influence the demand for beef, chicken, and eggs. Income disparities affect substitution patterns, wherein rising chicken prices lead to increased beef consumption, while eggs complement beef and premium varieties are perceived as luxury goods. Consequently, there is a necessity for policies addressing regional economic disparities, food security, and affordability, especially as premium products such as organic eggs become more prevalent and the cost of animal proteins increases.